Electronic effects in the dissociative ionisation of pyrene clusters. Issue 6 (25th January 2023) - Garcia, Gustavo A.; Dontot, Léo; Rapacioli, Mathias; Spiegelman, Fernand; Bréchignac, Philippe; Nahon, Laurent; Joblin, Christine
Abstract : We present a combined experimental and theoretical study on the dissociative ionisation of clusters of pyrene that shows non-statistical behaviour and suggests that the role of excited states must be considered in the interpretation of the results. Abstract : We present a combined experimental and theoretical study on the dissociative ionisation of clusters of pyrene. We measured the experimental appearance energies in the photon energy range 7.2–12.0 eV of the fragments formed from neutral monomer loss for clusters up to the hexamer. The results obtained show a deviation from statistical dissociation. From electronic structure calculations, we suggest that the role of excited states must be considered in the interpretation of experimental results, even in these relatively large systems. Non-statistical effects in the dissociative ionization process of polycyclic aromatic hydrocarbon (PAH) clusters may have an impact on the assessment of mechanisms determining the stability of these clusters in astrophysical environments.